1991
DOI: 10.1111/j.1600-0447.1991.tb03153.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Hospital Anxiety and Depression Scale in Arab patients

Abstract: The Hospital Anxiety and Depression Scale (HADS) was administered to psychiatric outpatients with various diagnoses to assess its validity. The study was also designed to find out whether HADS can differentiate between diagnostic groups based on depression and anxiety symptoms. HADS was able to discriminate patients from controls at a sensitivity of 79% and specificity of 87%. HADS was much less sensitive, specific and diagnostically accurate in identifying anxiety and depressive disorders in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
2
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 11 publications
6
67
2
1
Order By: Relevance
“…In the literature, reported cut-off values change between 3 and 10 for anxiety, and 4 and 11 for depression subscores. [25][26][27][28][29]. Notably, El-Rufaie et al [25] and Hopwood et al [30] concluded that the HADS anxiety subscale is more sensitive and reliable than depression subscale.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, reported cut-off values change between 3 and 10 for anxiety, and 4 and 11 for depression subscores. [25][26][27][28][29]. Notably, El-Rufaie et al [25] and Hopwood et al [30] concluded that the HADS anxiety subscale is more sensitive and reliable than depression subscale.…”
Section: Discussionmentioning
confidence: 95%
“…HADS was developed by Zigmond and Snaith in 1983 (9) and widely used as an instrument for detecting states of anxiety and depression in a healthy population (19), psychiatric patients (20), or medically ill patients (21,22) such as those with stroke (23) and rheumatoid arthritis (24). Most studies indicated its validity and…”
Section: Discussionmentioning
confidence: 99%
“…Further, the HADS has been shown to be comparable with other self-report scales like the Centre for Epidemiologic Studies Depression Scale (CES-D), Zung Self-rating Depression Scale, or Beck Depression Inventory (BDI) (34)(35)(36). Validity, reliability, and predictive values for the HADS have been evaluated in nonNative patients with depression (23,28,32) and predicted Structured Clinical Interview for DSM-III-R (SCm) depression in Norwegian general practice patients (31).…”
mentioning
confidence: 99%
“…Our survey included the Hospital Anxiety and Depression Scale (HADS) (23) and the CAGE questionnaire (24). The HADS, intended for medical patients, has been used successfully with both psychiatric and medical hospitalized patients, in community clinics (25)(26)(27)(28)(29)(30)(31), and in several different cultural and other settings (26,(31)(32)(33). Further, the HADS has been shown to be comparable with other self-report scales like the Centre for Epidemiologic Studies Depression Scale (CES-D), Zung Self-rating Depression Scale, or Beck Depression Inventory (BDI) (34)(35)(36).…”
mentioning
confidence: 99%